Manajemen Pendidikan Perspektif Islam - Tatang Aulia Rahman; Mumtahanah, Nurotun; Rahman, M. Nashihul Umam (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract : The results that the authors found were that in the view of |Islamic |teachings, |everything |must |be |done |in |a |neat, |orderly |and |orderly |manner, |and |the |processes |must |be |followed |properly. |All |educational |personnel |must |be |managed |personally |according |to |their |respective |fields |and |expertise. |Management |is |a |field |of |knowledge |that |has |been |developed |and |applied |in |an |organization, |be |it |government, |corporate, |social |or |educational. |So |that |the |concept |of |education |management |in |an |Islamic |perspective |needs |to |be |known |as |follows: |first, |the |meaning |of |education |management |in |an |Islamic |perspective, |second, |the |basics |of |education |management |in |an |Islamic |perspective, |third, |the |function |of |education |management |in |an |Islamic |perspective. |In |the |world |of |education, |the |Islamic |perspective |is |inseparable |from |the |basics |of |management |and |management |functions |in |general, |so |that |the |functions |of |education |management |in |an |Islamic |perspective |are |as |follows, |first, |planning |in |education |management |in |an |Islamic |perspective |must |be |a |first |step |that |is |really |considered |by |managers |and |education |manager. |Second, |educational |management |organizations |from |an |Islamic |point |of |view |must |comply |with |the |principles |of |organizational |design |and |operate |in |freedom, |fairness |and |consideration. |Third, |the |direction |of |education |management |in |an |Islamic |perspective |must |be |based |on |religious |principles |for |colleagues, |so |that |a |person |is |enthusiastic |about |carrying |out |his |duties |seriously |and |accompanied |by |a |very |deep |sincerity. |Fourth, |supervision |of |education |management |in |an |Islamic |perspective |must |be |material |and |spiritual |in |nature, |monitoring |not |only |managers, |but |also |Allah |SWT, |using |humane |methods |that |support |human |dignity. Keywords: |Management, |Perspective, |Islamic.